The Utility of PEG3350 without Electrolytes for 2-Day Colonoscopy Preparation in Children - Jibaly, R.; LaChance, J.; Lecea, N. A.; Ali, N.; Weber, J. E. (European Journal of Pediatric Surgery, 2011)
Successful colonoscopy preparation requires a method which is easy to administer. Simplifying this technique would be useful for adult and pediatric gastroenterologists. Most cleanout agents are not well tolerated by children. Polyethylene glycol without electrolytes (PEG3350 without electrolytes) has been used for constipation and bowel cleanout, but has not been studied as 2-day preparation for colonoscopy in children. This study evaluates the dosing, effectiveness and satisfaction with PEG3350 without electrolytes as a 2-day cleanout for colonoscopy preparation in children.Parents of patients aged 5 years or older undergoing colonoscopies were approached for participation. All caretakers received standard instructions with a suggested food handout and a diary to track the doses of PEG3350 administered and to document other adjunct measures (suppository, enema). On the procedure day, parents and children completed appropriate satisfaction questionnaires. Post procedure, the physician rated the visualization of the mucosa. A pediatric gastroenterologist investigator and a second blinded pediatric gastroenterologist assessed the effectiveness using standard procedure photos.30 patients aged 5–16 years were recruited (15 males, 15 females). The majority of parents and children reported being “very satisfied” or “satisfied” with the preparation. The preparation was rated by the principal investigator and independent pediatric gastroenterologist as effective in all cases. The mean number of doses was 4.7 on Day 1 and 4.9 on Day 2. The average dose given was 1.90 g/kg/day.PEG3350 without electrolytes appears to be safe, effective, and well tolerated as a 2-day clean out for colonoscopy preparation in children with an average dose of 1.90 g/kg/day.
Keywords: colonoscopy preparation; dosing – polyethylene glycol without electrolytes; satisfaction – polyethylene glycol without electrolytes; effectiveness – polyethylene glycol without electrolytes